Springtail coloration at a finer scale: mechanisms behind vibrant collembolan metallic colours. Issue 180 (7th July 2021) - Vanthournout, Bram; Rousaki, Anastasia; Parmentier, Thomas; Janssens, Frans; Mertens, Johan; Vandenabeele, Peter; D'Alba, Liliana; Shawkey, Matthew
Abstract : The mechanisms and evolution of metallic structural colours are of both fundamental and applied interest, yet most work in arthropods has focused on derived butterflies and beetles with distinct hues. In particular, basal hexapods—groups with many scaled, metallic representatives—are currently poorly studied and controversial, with some recent studies suggesting either that thin-film (lamina thickness) or diffraction grating (longitudinal ridges, cross-ribs) elements produce these colours in early Lepidoptera and one springtail (Collembola) species. Especially the collembolan basal scale design, consisting of a single lamina and longitudinal ridges with smooth valleys lacking cross-ribs, makes them an interesting group to explore the mechanisms of metallic coloration. Using microspectroscopy, Raman spectroscopy, electron microscopy and finite-difference time-domain optical modelling, we investigated scale colour in seven springtail species that show clear metallic coloration. Reflectance spectra are largely uniform and exhibit a broadband metallic/golden coloration with peaks in the violet/blue region. Our simulations confirm the role of the longitudinal ridges, working in conjunction with thin-film effects to produce a broadband metallic coloration. Broadband coloration occurs through spatial colour mixing, which probably results from nanoscale variation in scale thickness and ridge height and distance. These results provide crucial insights into the colour production mechanisms in a basal scale design and highlight the need for further investigation of scaled, basal arthropods.